Pre-service Chemistry Teachers’ Mental Model of Colligative Properties for Nonelectrolyte Solutions - Kelly Sinaga; Debora S. Sitinjak; Friska J. Purba (Universitas Tadulako, 2021)
Mental models are representations that describe the understanding of the three levels of representation in chemistry, that is macroscopic, sub-microscopic, and symbolic. This study aims to obtain a general description of the mental model of pre-service chemistry teachers in the colligative properties of non-electrolyte solutions. The study was a descriptive research with 22 second-year FIP Chemistry Education students from Pelita Harapan University Tangerang. Data collection was carried out with research instruments in the form of diagnostic tests. The results of the study state that the average percentage level of representation is 67 % macroscopic level, 31% sub-microscopic level, and 72 % symbolic level. The results of this study indicate that students' understanding at the macroscopic and sub-microscopic level of the colligative properties of non-electrolyte solutions was low compared to chemical representations at a symbolic level. Meanwhile, the categories of mental models possessed by pre-service chemistry teachers in the topic of non-electrolyte colligative properties vary for each level of chemical representation. Based on the percentage at each level of representation, the mental model of chemistry teacher candidates with a symbolic model category is higher than the scientific model. The low mental model of the scientific model contributed to the understanding of the pre-service chemistry teachers that the concept of chemistry is not intact scientifically.